The Digitization of Web-based Music Theory Modules - Ramafisela, Lingga (Journal of Education Technology, 2020)
In the digital era, modules in the form of books are deemed ineffective and inefficient due to the demand for online and independent lectures. This turned out to be facing obstacles due to limitations in learning media. Digital modules are needed to support teaching and learning activities in music theory courses so that the material presented can be well integrated. Digitalization is the process of changing from printed media to electronic media. Therefore it is necessary to digitize the web-based music theory module which aims to facilitate the teaching and learning process. The digitization of web-based music theory modules can be an important component that supports the implementation of the online lecture program that is currently being proclaimed by the government and supports the environmentally friendly (paperless) movement. The next target to be achieved is the development of a web-based music theory module in the ISI Yogyakarta Music Education study program. The qualitative method used in this research is based on data obtained in the field, namely in the music theory class of the ISI Yogyakarta Music Education study program. The technique of collecting data is utilizing literature study, observation, and interviews. The data analysis process was carried out by reducing data, presenting data, and drawing conclusions. The existence of a web-based music theory module is expected to be useful. una for convenience, progress and effectiveness of teaching and learning activities. The results of this study indicate that the module meets certain criteria, such as independent, independent, independent, adaptive, and user-friendly instructional. Based on the research results, it can be concluded that the digitization of the web-based music theory module is one proof of digital transformation due to technological advances.